The necessary, albeit belated, transition to computerized cognitive assessment - Asensio, David; Duñabeitia, Jon Andoni (Frontiers in Psychology, 2023)
Cognitive assessment is a common and daily process in educational, clinical, or research settings, among others. Currently, most professionals use classic pencil-and-paper screenings, tests, and assessment batteries. However, as the SARS-CoV-2 health crisis has shown, the pencil-and-paper format is becoming increasingly outdated and it is necessary to transition to new technologies, using computerized cognitive assessments (CCA). This article discusses the advantages, disadvantages, and implications of this necessary transition that professionals should face in the immediate future, and encourages careful adoption of this change to ensure a smooth transition.